Risk of falls in people with chronic kidney disease and related factors - Thaís Carrera de Carvalho; Ariane Polidoro Dini
Objective: to identify the risk and prevalence of falls in the last year in chronic renal failure patients on hemodialysis; to associate the risk of falls with the fear of falling and socio-demographic-clinical variables. Method: association study. 131 individuals participated in the study. The Morse Falls Scale, the Fall Efficacy Scale and the Tilburg Frailty Indicator were used. The data were analyzed by linear regression, the level of significance adopted was 0.05. Results: 97.7% were at risk for falls and 37.4% had at least one fall per year, with a mean of 2.02. Extreme concern about falling was presented by women, patients with less education, amputees, and frail individuals. Diabetes, as a comorbidity, and people with difficulty or need for assistance for ambulance showed a significant increase in the occurrence of falls. Conclusion: high risk and high prevalence of falls were found in hemodialysis patients, greater in those with diabetes or mobility limitations. Fear of falling was identified especially in women and in people with less education. These findings challenge the role of preventing falls, both in hemodialysis sessions and in the adoption of strategies for activities of daily living that involve patients and their families.